A Comprehensive Investigation of Youth Deviance: Theoretical Distinction by Deviant Behavior Sub-Types. Issue 6 (3rd June 2017) - Kim, Jihoon; Lee, Yeungjeom; Leban, Lindsay
ABSTRACT: Scholars have critiqued the field of criminology as focusing too heavily on positioning theories against one another in competition to reveal a "general theory of crime." Such an approach assumes that the same factors influence all forms deviance, which is a problematic assumption, given that different forms of deviance can be influenced by different sets of factors. This study draws on two prominent criminological theories to specify the individual mechanisms driving several different forms of juvenile delinquency. Findings demonstrate the need for different theories of crime and deviance, and have implications for the way scholars approach and study theories in criminology.